A New Approach for Manufacturing Stochastic Pure Magnesium Foam by Laser Powder Bed Fusion: Fabrication, Geometrical Characteristics, and Compressive Mechanical Properties. Issue 12 (2nd August 2021) - Hwang, Yu-Jin; Kim, Kyu-Sik; AlMangour, Bandar; Grzesiak, Dariusz; Lee, Kee-Ahn
Abstract : Herein, stochastic pure magnesium foam using laser powder bed fusion (LPBF) is fabricated and its geometric characteristics and mechanical properties are investigated. As volumetric energy density (VED) increased from 20 to 40 J mm −3 by controlling process parameters, porosity changed to 42.7 and 40.5%, respectively. Furthermore, the average sizes of interior consolidated/pore areas were 154.6 μm/142.9 μm (20 J mm −3 VED) and 230.8 μm/182.2 μm (40 J mm −3 VED), respectively. Magnesium foam induces lack‐of‐fusion defects through variable control of the LPBF process, and as such defects are connected, open pore structures are suggested to be formed. Stochastic pure Mg foam is composed of a main α‐Mg phase and a small amount of MgO phases. Room temperature compression test results obtained compressive yield strengths of 37 MPa (20 J mm −3 ) and 46 MPa (40 J mm −3 ). Compared with conventional pure Mg foam with similar relative density, LPBF Mg foam had relatively greater mechanical properties. This is considered to be due to the fine twin‐like microstructure formed by rapid solidification during LPBF. In conclusion, with LPBF, a biocompatible Mg foam with an open pore structure and outstanding mechanical properties was manufactured efficiently. Abstract : Stochastic pure magnesium foam is manufactured by laser powder bed fusion process (LPBF). Magnesium foam induces lack‐of‐fusion defects through variable control of the LPBF process, and as such defects are connected, open pore structures are suggested to be formed. Mechanical properties of LPBF stochastic pure magnesium foam is superior to pure magnesium foam manufactured conventional process.